Involving older people in the design, development, and delivery of an innovative module on aging for undergraduate students. Issue 10 (2nd October 2016) - Tullo, Ellen; Greaves, Laura; Wakeling, Luisa
ABSTRACT: As the number of older people in society increases, gaining an awareness of the needs of an aging population is important for university students from all academic backgrounds. Using a multidisciplinary approach to aging, we developed a new teaching module (NU-AGE [Newcastle University Aging Generations Education]) aimed at students enrolled in all undergraduate degree programs at our university. In acknowledgement of the important role that members of the public can play in higher education, we recruited a team of older adults to help design and deliver the module. The curriculum was constructed through collaboration with older members of the public and students to outline both the pertinent challenges facing an aging society, and the positive aspects of aging. The team of older adults contributed to the development and delivery of a series of interactive teaching sessions for a cohort of undergraduate students and collaborated with evaluation of the module. Early analysis of evaluation data suggested that students and members of the public highly valued the opportunity to interact and exchange ideas about the importance of aging in society in a multidisciplinary environment.